Heat transfer improvement in a square duct with diagonal inclined ribs - Suwannapan, Supattarachai; Poomsalood, Ratsak; Promvonge, Pongjet; Jedsadaratanachai, Withada; Limkul, Thitipat (My University, 2014)
This research presents a numerical study of turbulent periodic flow and heat transfer in three-dimensional isothermal-fluxed square duct with diagonal inclined rib inserted. The fluid flow and heat transfer characteristics are presented for Reynolds numbers in the range of 4000 to 20,000. The computations based on the finite volume method, and the SIMPLE algorithm has been implemented. Effects of rib pitch ratios (0.5 to 2) at a single blockage ratio of 0.2 and attack angle of 60° on heat transfer and friction factor in the duct are examined and their results of the inclined rib are also compared with those of the smooth duct. It is found that the inclined rib provides higher heat transfer rate and friction factor than the smooth duct for all cases. In addition, the decreasing of the pitch ratio leads to the rise in the Nusselt number and friction factor. © (2014) Trans Tech Publications, Switzerland.
Keywords: Diagonal inclined rib; Friction factor; Heat transfer; Square duct